Ireland : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper and Statistical Appendix on Ireland examines the productivity growth in Irish traded and nontraded goods, and provides some rough estimates of the sort of wage and inflation differentials that would be predicted by a Balassa-Samuelson framework under certain growth assumptions for the future. The paper provides a framework for judging what sort of wage growth and inflation could be sustained over the medium term without leading to a loss of competitiveness. The paper also examines traded and nontraded productivity in Ireland.